Enhanced Hybrid Routing Protocol for Energy-Efficient Multipath Routing in Manets - Praba. R; Sedhuvignesh. M; Vishal; Sedhu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Mobile Ad Hoc Networks (MANETs) pose challenges in managing dynamic energy consumption and optimizing network lifetime. This study proposes an improved hybrid routing protocol by integrating situation-adaptive routing and energy-efficient multipath routing strategies. We identified two promising routing protocols, FF-AOMDV and STFDR. While FF-AOMDV minimizes energy consumption, it ignores loss of power, resulting in link failures and reduced MANET lifetime. To address this, we introduce PLA-AOMDV, which efficiently manages power loss and outperforms FF-AOMDV in experimental results. However, PLA-AOMDV needs enhancements in addressing link breakage and utilization. Thus, we propose ELA-AOMDV to maximize energy efficiency and load balancing, refining route selection for better outcomes. Experimental findings demonstrate ELA-AOMDV’s superiority over PLA-AOMDV in throughput, packet dropping rate, energy consumption, and network lifetime. Additionally, we present an Improved Hybrid Routing Protocol (IHRP), which combines DMR, AOMDV, OLSR, and AODV. Leveraging the strengths of these protocols, IHRP exhibits superior performance compared to AOMDV, ZRP, AODV, and OLSR. It proposed enhanced hybrid routing protocol effectively addresses the challenges of dynamic energy consumption and efficient multipath routing in MANETs, improving network performance and lifetime.